Wireless Sensor Networks Energy Effectively Distributed Target Detection. (15th July 2014) - Qi, Xiaogang; Wei, Peng; Liu, Lifang; Xie, Mande; Cai, Guoyong
The target detection is a kind of very important application of wireless sensor networks. In this paper, we propose an energy effective distributed multisensor target detection method, which is different from the existing single sensor target detection methods, and target is detected by multisensor cooperation scheme. The first algorithm presents a method of the time series discretization to solve the distance of the target detected by the first connected node. The detected information is aggregated in the aggregating node, and the optimal path by the second algorithm is built up to transmit the aggregated packets to the sink. According to the simulation results, the probability of the single node target detection is compared with that of the multisensor collaborative target detection, and the influence of the weight coefficient on average node energy consumption is analyzed. Furthermore, we provide the optimal data sampling period of target detection data.